Monkey see, monkey do? How do shifts in parental socio-economic class influence children's outcomes? - Jaimee Stuart; Gail Pacheco; Mary Hedges; Susan Morton (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2013)
This paper utilises the Aberdeen Children of the 1950s (ACONF) cohort to investigate how both perinatal factors and changes in a child's environment impacts on IQ development between the ages of 7 and 11 years. Two methodological frameworks were utilised; (1) linear and logistic regression, the latter of which enabled calculation of odds ratios to predict likelihood of IQ growth above or below the population average, and (2) latent growth curve modelling (LGCM) which permitted estimation of determinants of two latent factors: an intercept and slope (which in this case equated to IQ at age 7 and the predicted growth trajectory in IQ between age 7 and 11). Results from both approaches were consistent. All of the perinatal factors were found to predict initial levels of IQ and some (mother's age, parity, gestational age, and gender) were found to predict change in IQ over time. Interestingly, after controlling for relevant perinatal factors, we found the effect of a downward trajectory in socio-economic status (SES) was related to lower IQ at age 7, whereas upward mobility in SES was associated with the converse. Consequently, our results illustrate that while perinatal factors are important in determining IQ in early childhood, growth in intelligence does appear to be responsive to changes in a child's environment, in this case proxied by mobility of paternal SES.
Keywords: 330; intelligence; socio-economic mobility; childhood; life-course